MENGUJI TAJI IMPLEMENTASI KEBIJAKAN PEMBERIAN BANTUAN HIBAH KEPADA KELOMPOK MASYARAKAT DI KABUPATEN BADUNGENTASI KEBIJAKAN PUBLIK - Sukmawati, Ni Luh Putu Rita; Budiana, I Nyoman (Universitas Medan Area, 2020)
This article aims to review, describe and analyze the implementation of the grant aid policy, find out what factors influence the policy of providing grant assistance and find out the effects of providing grant assistance to community groups in Badung Regency. To achieve this goal several methods and techniques are used. The method used is descriptive qualitative research type. Data collection techniques using observation, interviews and documentation. The informant determination technique used was purposive sampling with the number of informants determined. This study concludes that the provision of grant assistance to community groups in Badung Regency has been implemented very well in accordance with the principles of justice, the principle of propriety, the principle of rationality, the principle of transparency, the principle of accountability and the principle of benefits for the community. There are several factors that influence the policy of granting aid to community groups, namely communication, resources, disposition and bureaucratic structure. The policy of providing grant assistance to community groups in Badung Regency has two impacts namely positive and negative impacts. Both impacts depend on how the Badung Regency community groups react to it.